Zoning of Natural and Man-Made Disasters for Relief and Rescue Centers Site Selection Using the Model Logic (Case Study: Guilan Rural Area) - Nejad, Mohammad Ali Rahimipour Sheykhani; Agha, Farzaneh Nasiri Jan; Khatami, Sayedeh Sakineh; Fattahzadeh, Yalda (Review of Environment and Earth Sciences, 2017)
Guilan Province with vast forest resources and abundant rainfall which sometimes causes flooding, fires, road accidents and earthquakes, besides its tourist attraction, high population density and dispersion of rural areas has faced with the problems that necessitate emergency response centers against unexpected disaster with a balanced and equitable access. In order to select stationary and mobile station sites the potential risks were identified at first and then danger zones were determined. Nine major risks including floods, earthquakes, mass movements, fires, road accidents, snow and blizzards, marine incidents, avalanches and war were paired compared using Analytical Hierarchy Process (AHP). Then proper sites were determined based on required standards for establishing relief and rescue centers using the model LOGIC. Finally, 49 and 34 points were proposed for establishing stationary and mobile centers, respectively. Also the radius of effective range for each center was calculated based on a maximum response time to the incident.